Fungal Diversity and Mycotoxins in Low Moisture Content Ready-To-Eat Foods in Nigeria - Ezekiel, Chibundu N.; Oyedele, Oluwawapelumi A.; Kraak, Bart; Ayeni, Kolawole I.; Sulyok, Michael; Houbraken, Jos; Krska, Rudolf (Frontiers in Microbiology, 2020)
Low moisture content ready-to-eat foods vended in Nigerian markets could be pre-packaged or packaged at point of sale. These foods are widely and frequently consumed across Nigeria as quick foods. Despite their importance in the daily diets of Nigerians, a comprehensive study on the diversity of fungi, fungal metabolite production potential, and mycotoxin contamination in the foods has not yet been reported. Therefore, this study assessed the diversity of fungi in 70 samples of low moisture content ready-to-eat foods (cheese balls, garri (cassava-based), granola (a mix of cereals and nuts) and popcorn) in Nigeria by applying a polyphasic approach including morphological examination, genera/species-specific gene marker sequencing and secondary metabolite profiling of fungal cultures. Additionally, mycotoxin levels in the foods were determined by LC–MS/MS. Fungal strains (n=148) were recovered only from garri. Molecular analysis of 107 representative isolates revealed 27 species belonging to 12 genera: Acremonium, Allophoma, Aspergillus, Cladosporium, Fusarium, Microdochium, Penicillium, Sarocladium, Talaromyces and Tolypocladium in the Ascomycota, and Fomitopsis and Trametes in the Basidiomycota. To the best of our knowledge Allophoma, Fomitopsis, Microdochium, Tolypocladium and Trametes are reported in African food for the first time. A total of 21 uncommon metabolites were found in cultures of the following species: andrastin A and sporogen AO1 in Aspergillus flavus; paspalin in A. brunneoviolaceus; lecanoic acid and rugulusovin in A. sydowii; sclerotin A in P. citrinum and Talaromyces siamensis; barceloneic acid, festuclavine, fumigaclavine, isochromophilons (IV, VI and IX), ochrephilone, sclerotioramin and sclerotiorin in P. sclerotium; epoxyagroclavine, infectopyron, methylorsellinic acid and trichodermamide C in P. steckii; moniliformin and sporogen AO1 in P. copticola; and aminodimethyloctadecanol in Tolypocladium. Twenty-four mycotoxins in addition to other 73 fungal and plant toxins were quantified in the foods. In garri, cheeseballs, popcorn and granola were 1, 6, 12 and 23 mycotoxins detected, respectively. Deoxynivalenol, fumonisins, moniliformin, aflatoxins and citrinin contaminated 37, 31, 31, 20 and 14% of all food samples, respectively. Overall, citrinin had the highest mean concentration of 1481 µg/kg in the foods, suggesting high citrinin exposures in the Nigerian populace. Fungal and mycotoxin contamination of the foods depend on pre-food and post-food processing practices.